PENGARUH MARKETING MIX TERHADAP MINAT BELI ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO SECONDSHITSTUFF DI YOGYAKARTA - Asiken, Amira Hamidah Putri; Subkhan, Muhammad (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
This study aims to determine the effect of marketing mix on repurchase intention with consumer satisfaction as an intervening variable at Secondshitstuff stores in Yogyakarta. The population in this study were consumers of Secondshitstuff stores in Yogyakarta with a sample taken of 110 respondents. This study uses a quantitative descriptive method using primary data obtained from distributing questionnaires. In this study using non-probability sampling technique. The results of this study indicate that product has no positive effect on repurchase intention, price has a positive effect on repurchase intention, promotion has no positive effect on repurchase intention, place has a positive effect on repurchase intention, consumer satisfaction has a positive effect on repurchase intention, product has an effect positive effect on consumer satisfaction, price does not have a positive effect on customer satisfaction, promotion has a positive effect on customer satisfaction, place has a positive effect on customer satisfaction, and consumer satisfaction is able to mediate product, promotion, and place on repurchase intention while consumer satisfaction is not able to mediate price on repurchase interest.